PENGARUH BUDAYA ORGANISASI, KEPUASAN KERJA, DAN GAYA KEPEMIMPINAN TERHADAP MOTIVASI KERJA KARYAWAN PADA HOTEL MEGA ANGGREK JAKARTA DI MASA PANDEMI COVID 19 - Clariza Febriandiny (2021)
This research is a quantitative research conducted with goal of understanding and showing the impact of organizational culture, job satisfaction, and leadership style on employee motivation at Mega Anggrek Hotel Jakarta during the Covid 19 pandemic, totaling 45 employee. The sampling technique used is Non Probability Sampling with a saturated sample type. Assistance application when processing data using SmartPLS 3.0 by conducting T Test and F Test, so that the output result can be known and statistically proven that: (1) Organizational Culture has a positive and significant influence on employee motivation at Mega Anggrek Hotel Jakarta during the pandemic Covid 19, (2) Job Satisfaction has a positive and significant influence on Work Motivation at Mega Anggrek Hotel Jakarta during the Covid 19 pandemic, (3) Leadership Style has a negative and significant influence on Employee Work Motivation at Mega Anggrek Hotel Jakarta during the Covid pandemic 19, (4) Organizational Culture, Job Satisfaction, and Leadership Style have joint influence and significant on the Work Motivation of employees at Mega Anggrek Hotel Jakarta during the Covid 19 pandemic. Keywords : Organizational Culture, Satisfaction Work, Leadership Style, and Work Motivation.